Motion Editing for Time-Varying Mesh. (17th March 2008) - Xu, Jianfeng; Yamasaki, Toshihiko; Aizawa, Kiyoharu
Abstract : Recently, time-varying mesh (TVM), which is composed of a sequence of mesh models, has received considerable interest due to its new and attractive functions such as free viewpoint and interactivity. TVM captures the dynamic scene of the real world from multiple synchronized cameras. However, it is expensive and time consuming to generate a TVM sequence. In this paper, an editing system is presented to reuse the original data, which reorganizes the motions to obtain a new sequence based on the user requirements. Hierarchical motion structure is observed and parsed in TVM sequences. Then, the representative motions are chosen into a motion database, where a motion graph is constructed to connect those motions with smooth transitions. After the user selects some desired motions from the motion database, the best paths are searched by a modified Dijkstra algorithm to achieve a new sequence. Our experimental results demonstrate that the edited sequences are natural and smooth.